People should also look after the people: relational values of wildlife and collectively titled land in Ilkisongo Maasai group ranches in Southern Kenya - Unks, R.; Goldman. M. J.; Mialhe, F.; Roque de Pinho, J. (Ecology and Society, 2021)
Categorically distinct instrumental values and non-instrumental “cultural” values of “nature” are central to ecosystemservices assessments and many wildlife conservation interventions alike. However, this approach to understanding the value of nature is at odds with social scientific understandings that see value as produced through social-ecological relations and processes. With a case study of Ilkisongo Maasai land users living in group ranches surrounding Amboseli National Park in southern Kenya, we apply a relational values approach to highlight the processes of valuation that shape how different people within Maasai society come to have different shared values of wildlife and collectively titled land. First, we detail how wildlife conservation efforts in Amboseli have affected social relations through uneven conservation decision-making processes and unequal distribution of benefits from conservation. Second, we detail how conservation practices have directly influenced changing relationships between people and wildlife. Neglect of elders’ common stances on how relations “ought” to be maintained (both human-human and human-nonhuman relations), and many Maasai residents’ views of the “ownership” of wildlife by a minority have both fueled resentment. We show that an ironic, unintended outcome is that conservation projects, which are intended to increase the “value” of wildlife for local people as a way to foster “coexistence” of people and wildlife on collectively titled lands, are instead contributing to an increased desire by some Maasai for wildlife to be spatially separated from people and livestock. Simultaneously, current conservation projects do not build upon practices that in Maasai views, enabled historical sharing of land with wildlife. Inequality and lack of participation have been highlighted as key limitations of many community-based conservation and human-wildlife conflict mitigation initiatives. We instead focus on how wildlife conservation interventions have contributed to changing human-human and human-nonhuman relations and have in turn impacted long-term Maasai perceptions of wildlife. We argue that an expanded consideration of relational values that emphasizes the inseparability of culture and nature, but also includes a central consideration of power dynamics, might overcome some limitations of previous valuation approaches.